Complementary Feeding Practices Among The Caretakers Of The Young Children At Kathmandu - Sapkota, Sochana; Shrestha, S (Journal of Chitwan Medical College, 2014)
Appropriate complementary feeding practices are very important for proper growth and development of children. The objective of this study was to find out knowledge and practices of complementary feeding among caretakers of young children. A cross sectional descriptive study was conducted by taking 195 caretakers of 6 to 24 months children of randomly selected wards of Ramkot, Sewchatar and Ichangunarayan VDC of Kathmandu district. Descriptive and inferential statistics (Chi square and McNemar test) were used for data analysis. Caretakers having adequate knowledge were 59.5%. Regarding practices, 83.65% had continuing breastfeeding. Only 33.3% of caretakers had started complementary feeding at 6 months even though the72.3% had knowledge on it. Children having minimum meal frequency were 64.65%, minimum dietary diversity were 72.3% and minimum acceptable diet were 52.30%. Practice of feeding Vitamin A rich fruits and vegetables was only 3.1%. In observation, most of the caretakers were doing as they said the interview showing no statistical significance by McNemar test. Occupation (p=0.015), literacy status (p=0.000) and economic status (p=0.000) have the association with the complementary feeding knowledge. Similarly economic status, literacy status and age of caretakers were significantly associated with most of the feeding practices. The knowledge levels as well as most of the feeding practices were found good in caretakers of young children. But the large gaps were found in the initiation of complementary feeding and feeding vitamin A rich fruits and vegetables. Journal of Chitwan Medical College 2013; 3(4); 25-29 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9550